2023
DOI: 10.1039/d2cp05794h
|View full text |Cite
|
Sign up to set email alerts
|

Bilayer tetragonal AlN nanosheets as potential cathodes for Li–O2 batteries

Abstract: Li-O2 batteries are considered promising electrochemical energy storage devices due to their high specific capacity and low cost. However, this technology currently has two serious problems: low round-trip efficiency and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…51 Recently, the study about bilayer tetragonal AlN nanosheets as cathode catalysts for Li− O 2 batteries exhibited extremely low overpotential and dissociation energy barriers. 52 In a previous work, we have predicted two new two-dimensional materials, bilayer tetragonal Si 2 Se 2 and SiSe 2 , which are thermodynamically and dynamically stable, by means of phonon spectroscopy and molecular dynamics. 53 Because Si 2 Se 2 and SiSe 2 have suitable affinity with Li + , Na + , and K + , they can act as potential anode materials for alkali metal-ion batteries.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…51 Recently, the study about bilayer tetragonal AlN nanosheets as cathode catalysts for Li− O 2 batteries exhibited extremely low overpotential and dissociation energy barriers. 52 In a previous work, we have predicted two new two-dimensional materials, bilayer tetragonal Si 2 Se 2 and SiSe 2 , which are thermodynamically and dynamically stable, by means of phonon spectroscopy and molecular dynamics. 53 Because Si 2 Se 2 and SiSe 2 have suitable affinity with Li + , Na + , and K + , they can act as potential anode materials for alkali metal-ion batteries.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In 2017, Ji et al designed two two-dimensional (2D) monolayer GeS and GeSe structures, and the results showed that GeSe has a low overpotential and is an excellent candidate for nonaqueous Li–O 2 battery cathode materials . Recently, the study about bilayer tetragonal AlN nanosheets as cathode catalysts for Li–O 2 batteries exhibited extremely low overpotential and dissociation energy barriers . In a previous work, we have predicted two new two-dimensional materials, bilayer tetragonal Si 2 Se 2 and SiSe 2 , which are thermodynamically and dynamically stable, by means of phonon spectroscopy and molecular dynamics .…”
Section: Introductionmentioning
confidence: 99%